The Social Relevance of Ḥassān Ḥanafī's and Nurcholish Madjid's Thoughts: A Sociological Analysis in the Context of Islam in Indonesia - Ardiansyah, Andri; Alkosibati, Ali (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to analyze the reformist thoughts of Ḥassan Ḥanafī and Nurcholish Madjid in the context of modern civilization and the challenges facing the Islamic world. The research problem focuses on how the thoughts of these two figures can provide solutions to essays in science, philosophy, and the dynamics of Islam's relationship with the state. This research uses qualitative methods with a literature study approach and descriptive analysis. The research results show that Ḥanafī's thoughts on Occidentalism and Madjid's thoughts on secularization and modernization offer important contributions to Islamic reform. The research recommendation is to continue exploring their thoughts to understand their impact on contemporary Islamic society.